Mouse superkiller‐2‐like helicase DDX60 is dispensable for type I IFN induction and immunity to multiple viruses. Issue 12 (12th October 2015) - Goubau, Delphine; van der Veen, Annemarthe G.; Chakravarty, Probir; Lin, Rongtuan; Rogers, Neil; Rehwinkel, Jan; Deddouche, Safia; Rosewell, Ian; Hiscott, John; Reis e Sousa, Caetano
Abstract: IFN‐α/β allow cells to fight virus infection by inducing the expression of many genes that encode effectors of antiviral defense. One of these, the Ski2‐like DExH‐box helicase DDX60, was recently implicated in resistance of human cells to hepatitis C virus, as well as in induction of IFN‐α/β by retinoic acid inducible gene 1‐like receptors (RLRs) that detect the presence of RNA viruses in a cell‐intrinsic manner. Here, we sought to investigate the role of DDX60 in IFN‐α/β induction and in resistance to virus infection. Analysis of fibroblasts and myeloid cells from Ddx60 ‐deficient mice revealed no impairment in IFN‐α/β production in response to RLR agonists, RNA viruses, or other stimuli. Moreover, overexpression of DDX60 did not potentiate IFN induction and DDX60 did not interact with RLRs or capture RLR agonists from virally infected cells. We also failed to identify any impairment in Ddx60‐deficient murine cells or mice in resistance to infection with influenza A virus, encephalomyocarditis virus, Sindbis virus, vaccinia virus, or herpes simplex virus‐1. These results put in question the reported role of DDX60 as a broad‐acting positive regulator of RLR responses and hint at the possibility that it may function as a restriction factor highly specific for a particular virus or class of viruses.